2023
DOI: 10.1177/03331024221146985
|View full text |Cite
|
Sign up to set email alerts
|

Epicranial headache part 1: Primary stabbing headache

Abstract: Background/objective Primary stabbing headache is a common but under-recognized primary headache disorder. The objectives of this review were to provide practical information for better understanding and identification of the disease, suggest an algorithm for differential diagnosis, and provide an insight into the pathophysiology of primary stabbing headache hypothesized from its clinical course. Methods This narrative review of primary stabbing headache is based on a literature search and the authors’ clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
11

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 65 publications
0
13
0
11
Order By: Relevance
“…NH is not as frequent as other prevalent headache disorders, such as tension-type headache or migraine, but its incidence could be estimated to be 8.6 cases per 100,000 patient-years, an estimation similar to those of central nervous system cancer (11 cases per 100,000 patient-years), myelopathies (13 cases per 100,000 patient-years) and amyotrophic lateral sclerosis (5 cases per 100,000 patient-years) (17). Previous studies have reported data on the clinical phenotype of NH and the patient response to treatment (1,3,6,10,18), but its long-term nature has not yet been characterized (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NH is not as frequent as other prevalent headache disorders, such as tension-type headache or migraine, but its incidence could be estimated to be 8.6 cases per 100,000 patient-years, an estimation similar to those of central nervous system cancer (11 cases per 100,000 patient-years), myelopathies (13 cases per 100,000 patient-years) and amyotrophic lateral sclerosis (5 cases per 100,000 patient-years) (17). Previous studies have reported data on the clinical phenotype of NH and the patient response to treatment (1,3,6,10,18), but its long-term nature has not yet been characterized (5).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the proportion of patients with prior history of migraine was slightly higher than expected in our setting because the prevalence of migraine in Spain is 12.6% (24) and 17.2% of patients in our population had a previous history of migraine. On the other hand, NH is frequently associated with epicrania fugax (5,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary stabbing headache (PSH) belongs to this group and is perhaps the most common primary headache after migraine and tension-type headache in the general population. Kwon et al reviewed the epidemiology and symptomatology of stabbing headaches (4). Even though secondary headaches may sometimes present with stabbing features, the majority of patients have a primary headache and self-limiting disease course.…”
Section: Other Primary Headaches: Distinct Clinical Features and Unce...mentioning
confidence: 99%
“…Kwon et al. reviewed the epidemiology and symptomatology of stabbing headaches (4). Even though secondary headaches may sometimes present with stabbing features, the majority of patients have a primary headache and self-limiting disease course.…”
mentioning
confidence: 99%